The cross-sectional study of anxiety levels and ratio of severity of thirteen symptoms of anxiety among medical students - Iqbal, Muhammad Arslan; Abbas, Muhammad Waseem; Chaudhary, Muhammad Zohaib; Iqbal, Muhammad Nouman; Aleem, Mohammad Sami; Javaid, Rukhsar; Ahmed, Hasnain; Younas, Taleea; Maqsood, Faiza; Fatima, Fiza; Ahmed, Hafiz Hasnain; Mushtaq, Sana (International Journal of Research in Medical Sciences, 2017)
Background: Anxiety is defined as physical, behavioral, social and psychological response to treat self-concept characterized by subjective, consciously perceived feelings of tension. Nowadays anxiety is most commonly found among medical students. This study was conducted to find out the anxiety levels and ratio of severity of thirteen symptoms of anxiety. Methods: A questionnaire based study was conducted among 178 medical students which tests the level of anxiety and severity of symptoms of anxiety. The questionnaire used was hamilton anxiety rating scale (HAM-A). Results: Out of 178 students, 80 (44.94%) students scored mild anxiety levels, 63 (35.39%) students scored moderate anxiety levels and 35 (19.66%) students scored severe anxiety levels. Conclusions: Mild form of anxiety is much more common among medical students and majority of these medical students are females. Moreover, the symptoms of anxiety including tension, anxious mood, depressed mood, insomnia, fear and CVS symptoms appear with moderate severity in majority of medical students while on the other hand some symptoms including general somatic muscular and sensory symptoms, difficulties in concentration and memory, genitor-urinary symptoms, respiratory symptoms, GIT symptoms and other autonomic symptoms appear with least severity among majority of medical students.